2005
DOI: 10.1002/em.20153
|View full text |Cite
|
Sign up to set email alerts
|

Improved single-cell gel electrophoresis assay for detecting DNA damage inEisenia foetida

Abstract: The earthworm (Eisenia foetida) is an attractive sentinel species for detecting genotoxicity in soil. In this study, an improved single-cell gel electrophoresis (SCGE) assay was developed for detecting DNA damage in the coelomocytes (lymphocytes) of earthworms. Coelomocytes were obtained from the coelomic fluid using a modified extrusion medium that did not include the mucolytic agent guaiacol. The extruded coelomocytes contained at least three types of cells: eleocytes (75% of the total), amoebocytes, and gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 14 publications
(15 reference statements)
0
21
0
4
Order By: Relevance
“…Di Marzio et al [2005] observed no genotoxic effect on earthworms after 2 and 7 days of exposure but after 15 and 21 days of exposure to a PAH-contaminated soil with concentrations 5 or 10 times below ours (S 16 PAHs 5 96 mg/kg d.w.). Qiao et al [2007] demonstrated genotoxicity in earthworms after 1, 3, 7, and 14 days of exposure to soils irrigated by wastewaters contaminated with PAHs and other persistent organic compounds.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Di Marzio et al [2005] observed no genotoxic effect on earthworms after 2 and 7 days of exposure but after 15 and 21 days of exposure to a PAH-contaminated soil with concentrations 5 or 10 times below ours (S 16 PAHs 5 96 mg/kg d.w.). Qiao et al [2007] demonstrated genotoxicity in earthworms after 1, 3, 7, and 14 days of exposure to soils irrigated by wastewaters contaminated with PAHs and other persistent organic compounds.…”
Section: Discussionmentioning
confidence: 85%
“…Yet, studies dealing with the genotoxicity of field-contaminated soils to earthworms are rare [White and Claxton, 2004]. Few authors have studied the genotoxicity to earthworms of PAH-contaminated soils [Šalagovič et al, 1996;Di Marzio et al, 2005] or multicontaminated field soils [Verschaeve and Gilles, 1995;Xiao et al, 2006b;Qiao et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were performed in triplicate and 900 cells were analyzed per each fish. Only comets with similar size and shape nuclei were scored to avoid heterogeneous response of differing cell types present in the cell suspension [22].…”
Section: Onestep Rt-pcrmentioning
confidence: 99%
“…Cell viability was determined using 0.4% of Trypan blue. A single-cell electrophoresis assay (SCEA) was carried out according to Di Marzio et al [22]. Basically, the gels were composed of three layers of agarose.…”
Section: Onestep Rt-pcrmentioning
confidence: 99%
“…This result was consistent when the process of brown body formation (by aggregation of coelomocytes) was considered (Valembois et al 1992). This relation could be supported indirectly by the findings, including the dependence of the quantitative composition of coelomocytes on individual age, which was mentioned in some studies (Adamowicz and Wojtaszek 2001;Di Marzio et al 2005). On the contrary to the findings mentioned above, Dales (1964) reported that the size of coelomocytes changed independently from the body size of an adult during the growth.…”
Section: Discussionmentioning
confidence: 72%